Could Guillain–Barré syndrome be triggered by COVID‐19 vaccination? - Maya Aldeeb (14777215) (2023)
Due to SARS-COV-2 (COVID-19) pandemic and its catastrophic impact on society, the FDA granted emergency use authorization for some vaccines. Possible rare side effects could not have been observed in this relatively short period. We are reporting an elderly lady with multiple comorbidities who presented with progressive lower limb weakness that started seven days after receiving the first dose of the COVID-19 vaccine. The electrodiagnostic study showed demyelinating polyneuropathy with secondary axonal degeneration consistent with Guillain–Barré syndrome. We ruled out other possible causes for GBS, suggesting a postvaccine nature for her presentation. The patient received intravenous immunoglobulin (IVIG) for five days and gradually improved, which supports our initial diagnosis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5237